A Cellular Fusion Cascade Regulated by LaeA Is Required for Sclerotial Development in Aspergillus flavus - Zhao, Xixi; Spraker, Joseph E.; Bok, Jin Woo; Velk, Thomas; He, Zhu-Mei; Keller, Nancy P. (Frontiers in Microbiology, 2017)
Aspergillus flavus is a saprophytic soil fungus that poses a serious threat worldwide as it contaminates many food and feed crops with the carcinogenic mycotoxin called aflatoxin. This pathogen persists as sclerotia in the soil which enables fungal survival in harsh environmental conditions. Sclerotia formation by A. flavus depends on successful cell communication and hyphal fusion events. Loss of LaeA, a conserved developmental regulator in fungi, abolishes sclerotia formation in this species whereas overexpression (OE) of laeA results in enhanced sclerotia production. Here we demonstrate that sclerotia loss and inability to form heterokaryons in A. flavus ∆laeA is mediated by homologs of the Neurospora crassa ham (hyphal anastomosis) genes termed hamE-I in A. flavus. LaeA positively regulates ham gene expression and deletion of hamF, G, H, or I phenocopies ∆laeA as demonstrated by heterokaryon and sclerotia loss and reduced aflatoxin synthesis and virulence of these mutants. Deletion of hamE showed a less severe phenotype. hamE-I homologs are positively regulated by the clock controlled transcription factor ADV-1 in N. crassa. Similarly, the ADV-1 homolog NosA regulates hamE-I expression in A. flavus, is required for sclerotial development and is itself positively regulated by LaeA. We speculate that a putative LaeA>NosA>fusion cascade underlies the previously described circadian clock regulation of sclerotia production in A. flavus.